(untitled) (Global Journal of Medical Research, 2014)
Introduction-Hundreds of millions of people worldwide are affected by mental, behavioral, neurological and substance abuse disorders. For example, estimates made by WHO in 2002 showed that 154 million people globally suffer from depression and 25 million people from schizophrenia. (1) This exerts tremendous social, medical and financial burden. Early intervention and effective management can easily reduce this burden significantly. One other main disorders encountered and constitute real challenge are the psychotic disorders. They constitute 3 to 4 % of all mental disorders (1). They have gained special interest due to its possible chronic course and hence its long term economic and social impact. Cost-effective treatments exist for most disorders and, if correctly applied, could enable most of those affected to become functioning members of society.